First Trimester Diagnosis of Holoprosencephaly Secondary to a Ring Chromosome 7 - Lindsay B. Henderson; Virginia L. Corson; Daniel O. Saul; Cynthia Anderson; Sarah Millard; Denise A. S. Batista; Karin J. Blakemore; Cheryl DeScipio (Case Reports in Genetics)
Holoprosencephaly (HPE) is a developmental defect in humans in which the forebrain fails to completely separate into two hemispheres. We describe a 12 3/7-week-old fetus found on ultrasound evaluation to have features consistent with HPE, including a single anterior ventricle, fused thalami, and a flattened profile. Cytogenetic analysis of chorionic villi revealed a ring chromosome 7 [r(7)]. This uncommon finding has been associated with growth delay, microcephaly, and dermatologic abnormalities. However, both the clinical features and the extent of cytogenetic imbalance of chromosome 7 are variable, and few reported cases of r(7) have been molecularly studied. To our knowledge, this is the first report of a prenatally identified r(7), molecularly characterized using array comparative genomic hybridization.